LOGANOGRAPTUS FLAGELLATUS NOV. SP. EN LA FORMACIÓN GUALCAMAYO (ORDOVÍCICO), PRECORDILLERA DE SAN JUAN, ARGENTINA (Ameghiniana, 2014)
A new species of the genus Loganograptus is here described. The graptolite is characterized by its long stipes (whip-Iike stipes), and the morphology of the thecae: long and narrow but expanding at the aperture. The specimens were collected in the lower beds of the Guaicamayo Formation, referred to the late Arenigian (Undulograptus austrodentatus Zone).